Improving management of patients with hyperemesis. Issue 2 (25th October 2013) - Lloyd, Jilly; Ramskill, Nikki; Sharma, Bhavna
Abstract: Hyperemesis gravidarum (HG), defined as severe nausea and vomiting resulting in dehydration, is a common reason for emergency admission in gynaecology (1). The management of HG is supportive, including the correction of dehydration and electrolyte disturbances and use of antiemetics. An audit in our unit identified that women with HG were not receiving appropriate fluid resuscitation and in particular inadequate potassium replacement. A proforma was developed by a multidiscplinary team to prompt appropriate investigations, medications, and fluid resuscitation. The proforma was introduced in paper format and electronically, accompanied by an education programme for junior doctors. This intervention has improved prescribing practice and fluid resuscitation for these patients. Length of admission has reduced. Efforts have been made to ensure this change is sustainable in the long term, through involvement of the junior doctors using the proforma at all stages of the project.